Development of a new carbon nanotube–alginate–hydroxyapatite tricomponent composite scaffold for application in bone tissue engineering - Rajesh R (Dove Medical Press, 2015)
Rajendiran Rajesh, Y Dominic Ravichandran Organic Chemistry Division, School of Advanced Sciences, VIT University, Vellore, India Abstract: In recent times, tricomponent scaffolds prepared from naturally occurring polysaccharides, hydroxyapatite, and reinforcing materials have been gaining increased attention in the field of bone tissue engineering. In the current work, a tricomponent scaffold with an oxidized multiwalled carbon nanotube (fMWCNT)–alginate–hydroxyapatite with the required porosity was prepared for the first time by a freeze-drying method and characterized using analytical techniques. The hydroxyapatite for the scaffold was isolated from chicken bones by thermal calcination at 800°C. The Fourier transform infrared spectra and X-ray diffraction data confirmed ionic interactions and formation of the fMWCNT–alginate–hydroxyapatite scaffold. Interconnected porosity with a pore size of 130–170 µm was evident from field emission scanning electron microscopy. The total porosity calculated using the liquid displacement method was found to be 93.85%. In vitro biocompatibility and cell proliferation on the scaffold was checked using an MG-63 cell line by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and cell attachment by Hoechst stain assay. In vitro studies showed better cell proliferation, cell differentiation, and cell attachment on the prepared scaffold. These results indicate that this scaffold could be a promising candidate for bone tissue engineering. Keywords: chicken bone, hydroxyapatite, alginate, tissue engineering